Fracturing, block faulting, and moulin development associated with progressive collapse and retreat of a maritime glacier: Falljökull, SE Iceland. Issue 3 (19th August 2013) - Phillips, Emrys; Finlayson, Andrew; Jones, Lee
Abstract [1] Since 2007, Falljökull in southeast Iceland has been undergoing passive downwasting, providing an ideal opportunity to study a range deformation structures developed in response to ice‐marginal collapse and retreat. An integrated terrestrial lidar, Ground Penetrating Radar, and glaciological structural study of the clean, debris‐free ice at the margin of Falljökull has allowed a detailed model of the surface and subsurface 3D structure to be developed. Collapse of the glacier margin takes the form of a multiple rotational failure controlled by large‐scale, down‐ice dipping normal faults. As the fault‐bound blocks of ice are displaced downslope, they rotate leading to localized compression and the formation of down‐faulted graben‐like structures. Moulins present within the marginal zone of Falljökull are closely associated with the zones of relatively more intense brittle deformation which crosscut the glacier. A model is proposed where the moulins have formed in response to the progressive collapse of englacial drainage channels located along down‐ice dipping normal faults. The preferential development of the moulins and englacial drainage channels along the normal faults weakens the ice along these structures, promoting or even accelerating further collapse of the ice margin. The complex pattern of surface lowering within the marginal zone of Falljökull has also been shown to be directly related to movement on the main faults controlling the collapse of the ice margin. This evidence suggests that structurally controlled collapse may, in some instances, have a profound effect on glacier surface lowering and geodetic mass balance measurements.